Effectiveness of Purification Used Cooking Oil Using Adsorbents: Activated Charcoal Seeds Salak (Salacca zalacca) - Sufia, Sufia; Santoso, Tri; Aminah, Sitti; Rahmawati, Sitti (Universitas Tadulako, 2023)
Salak seeds have a reasonably high cellulose content. This suggests that salak seeds can be used as a raw material for producing activated charcoal to refine used cooking oil. This study aims to determine the effectiveness of refining used cooking oil using active charcoal adsorbents derived from Salacca zalacca seeds. The methods used to determine free fatty acid levels and peroxide values are the acid-base and iodometric titration methods. This study will observe several variables that affect the adsorption process, namely the mass of activated charcoal and the contact time of used cooking oil. The results showed a decrease in free fatty acids and peroxide number, and the colour of the oil became brighter with increasing adsorbent and contact time. The best results were obtained at a mass of 15 grams and an adsorption time of 120 minutes. Based on the quality requirements for cooking oil as specified in SNI 3741-1995.